A study to know the various causes of pleural effusion and role of pleural fluid adenosine deaminase enzyme in tuberculous pleural effusion - Kumar, Avdhesh; Kumar, Brijesh; Verma, Sanjay Kumar; Kumar, Anand; Mathur, R. K.; Chaudhry, Sudhir; Kant, Surya (International Journal of Research in Medical Sciences, 2020)
Background: India has the maximum burden of both non MDR tuberculosis (TB) and Multidrug-Resistant (MDR) TB, as per data reported in Global TB Report 2018 and tuberculosis is remains one of the most common cause of pleural effusions. Methods: This was a cross-sectional study conducted in Department of Respiratory Diseases and a total of 110 patients with pleural effusion were included in the study, which were enrolled for treatment from July 2018 to June 2019. Results: One hundred and ten patients with pleural effusion were enrolled during the study period. There were 65 males (59%) and 45 (40.9%) females. The overall mean age for males and females were 44.4±18.84 years (35-87 years) and 38.28±17.66 years (35-87 years) respectively. Tuberculous Pleural Effusion group (TPE) seen in 82 patients. Right sided pleural effusion (69.5 %) were more common than left sided (30.4 %). In TPE group the mean pleural fluid ADA level were 86.41±38.08 IU/L (range: 14-195 IU/L). The Malignant Pleural Effusion (MPE) group included 21 patients. In MPE group the mean pleural fluid ADA level were 34.10±32.88 IU/L (range: 8-144 IU/L). The difference in pleural fluid ADA levels between TPE and MPE group was statistically highly significant. Conclusions: Tuberculous pleural effusion was the most common cause of pleural effusion in present study and observed in 74.5% cases.